GLOBALIZATION AND ETHNOMUSICOLOGY - Omarova Aklima; Kaztuganova Ainur; Karomat Dilorom (Scientific Journal of Pedagogy and Economics, 2020)
The interpretation of the category “genre” which is presented based on the classification of makom, due to its internal nature, causes disagreement among the scholars, and difficulties due to its designation of a specific type of work and/or national art form. In particular, the emphasis on circumstances related to the centuries-old, extended, regional, situational development in line with the oral tradition and in the frame of improvisational art, and the definition of the national type of musical art as a “genre” lead to disproportionate indicators in theoretical issues. In this regard, the reasons for the incorrect use of the category “genre” in the studies of the Kazakh kuy art were commented: in one case, it is correlated as a whole with the “kuy” phenomenon, in the other, it is used in relation to certain phenomena arising from the study of its internal distinctive nature. The “Triad of factors” – multivariance, cyclicity and locality – which formed the basis for conceptual generalizations of the famous musicologist T.B. Gafurbekov in the works revealing its system-forming nature in monodic culture is shown in conjunction with principles that reflect the genre specificity of instrumental music of the Kazakhs. The groups of macrovolume can include “Akzhelen”, “Kosbasar”, “Nauayi”, the microvolume barnch by Kurmangazy “Kisen ashkan”, “Kobіk shashkan”, “Turmeden kashkan” etc. The regional kuys with the same name by Kurmangazy, Dauletkerey, Dina “Zhiger” can be cited as an example. The situational kuys include “Kenes”, “16-zhyl” etc. As a final conclusion, the importance of considering the art of the Kazakh kuy in the system of monodic cultures and a new “clarification” of its inner nature is emphasized. From this point of view, the theoretical concept of T.B. Gafurbekov is updated as capable of forming a common scientific platform for studying the traditions of the Turkic-speaking peoples based on improvisation.